THE EFFECT OF DIGITAL SKILLS ON EMPLOYEE PERFORMANCE MEDIATED BY INNOVATIVE BEHAVIOR IN DIGITAL COMPANIES IN JABABEKA CIKARANG INDUSTRIAL ESTATE - Asep Saeful; Ekhsan, Muhamad (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2024)
This study aims to analyze the effect of digital skills on employee performance mediated by innovative behavior in digital companies in the Jababeka Industrial Estate. The population used in this study are employees of digital companies in the JABABEKA Cikarang industrial area. to determine the sample size, this study used the probality sampling method simple random sampling, so that 85 respondents were obtained. This quantitative research uses Partial Least Square (PLS) as a data analysis technique. The results showed that digital skills have a significant positive effect on employee performance. innovative behavior has a significant positive effect on employee performance. digital skills have a significant positive effect on innovative behavior. digital skills have a significant positive effect on employee performance through the mediating role of innovative behavior. This research provides important implications for digital companies in designing digital skills development programs and encouraging innovative behavior to improve employee performance.